Cultural values in traditional Talo Balak music at Sanggar Kerthi Buana, Bandar Lampung - I Gusti Putu Agung Eka Wira Setiadi; Widodo Widodo; Suharto Suharto (Universitas Muhammadiyah Enrekang, 2023)
AbstractCultural values are a representation of values that have been ingrained and agreed upon by a group of people as the way they behave. Culture is a whole which includes beliefs, values, technology, customs, skills and habits as a result of humans' meaning in their lives. The aim of this research is to reveal the cultural values of Talo Balak Traditional Music at Sanggar Kherti Buana, Bandar Lampung. This research uses an inter-disciplinary approach with sociocultural theory. This research uses a qualitative method with a research design, namely a case study. The focus of this study is to examine more deeply the cultural values of traditional Talo Balak music at the Kherti Buana studio. The research location chosen in this study was the Kherti Buana art studio, Bandar Lampung. The results of the discussion in this research are that Talo Balak music contains local cultural values such as the value of tolerance, the value of mutual cooperation, the value of hard work, and the value of courtesy, whichbased on Piil Pesenggiri's philosophy of life.Keywords:Traditional Music, Cultural Values, Talo Balak. ABSTRAKNilai budaya adalah representasi nilai-nilai yang telah mengakar dan disetujui oleh sekolompok masyarakat sebagai cara mereka berperilaku. Budaya merupakan sebuah keutuhan yang didalamnya mencakup kepercayaan, nilai, teknologi, adat istiadat, keterampilan dan kebiasaan sebagai hasil dari pemaknaan manusia dalam kehidupannya. Tujuan penelitian ini adalah mengungkap nilai-nilai Budaya pada Musik Tradisional Talo Balak di Sanggar Kherti Buana, Bandar Lampung. Penelitian ini menggunakan pendekatan inter-desipliner dengan teori sosiokultural. Penelitian ini menggunakan metode kualitatif dengan desain penelitian yaitu studi kasus. Fokus pada kajian ini adalah menelisik lebih dalam terkait nilai-nilai Budaya pada musik tradisional Talo Balak di sanggar Kherti Buana. Lokasi penelitian yang dipilih dalam kajian ini yaitu sanggar seni Kherti Buana, Bandar Lampung. Hasil pembahasan dalam penelitian ini adalah music Talo Balak memuat nilai-nilai Budaya lokal seperti nilai toleransi, nilai gotong-royong, nilai kerja keras, dan nilai sopan santun, yang berlandaskan pada filsafat hidup Piil Pesenggiri. Kata Kunci: Music Tradisional, Nilai Budaya, Talo Balak.